Ning de Coninck-Smith, Bengt Sandin and Ellen Schrumpf (eds.): Industrious Children. Work and Childhood in the Nordic Countries 1850-1990. (Odense University Press, 1997). 211 s., 250 kr. - Rostgaard, Marianne (Historie Jyske Samling, 2000)
-